Takwil As-Sirāṭ Al-Mustaqīm dalam Pembacaan Tafsir Mulla Sadra - Nurul Khair; Ahmed Zaranggi Ar Ridho; Siti Hadaynayah Salsabila (Qur'an and Hadith Academic Society, 2020)
This paper is a literature review of Mullā Ṣadrā's thoughts on takwil as-ṣirāṭ al-mustaqīm which is studied through his main work, entitled Tafsīr Al-Qur'ān Al-Karīm. By using the descriptive-analytical method, the conclusion is that takwil as-ṣirāṭ al-mustaqīm in Mullā Ṣadrā's view is studied through two approaches, namely the text analysis method and mukāshafah as a process of knowing the true meaning of the term as-ṣirāṭ al-mustaqīm. In discourse, it is known that the commentators are divided into two views, namely the historical view which examines the term as-ṣirāṭ al-mustaqīm based on textual narrations and the view of ijtihad based on rationality. The implication of these two views is to limit the meaning and essence of the term as-ṣirāṭ al-mustaqīm based on historical and intellectual references. In order to overcome these problems, this paper aims to explain the nature and meaning of as-ṣirāṭ al-mustaqīm based on Mullā Ṣadrā's takwil by mediating historical and rational views. The result of this paper is to offer a new perspective on understanding the terms of the Qur’an transcendentally so that each individual can clearly understand the meanings and nature of as-ṣirāṭ al-mustaqīm.